2011
DOI: 10.1590/s0037-86822011005000009
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antimicrobial resistance among clinical isolates of enterococci in a Brazilian tertiary hospital: a 4-year study

Abstract: Introduction: In the past two decades members of the genus Enterococcus have emerged as important nosocomial pathogens worldwide. This study prospectively analyzed the distribution of species and trends in antimicrobial resistance among clinical isolates of enterococci in a Brazilian tertiary hospital from 2006-2009. Methods: Enterococcal species were identified by conventional biochemical tests. The antimicrobial susceptibility profile was performed by disk diffusion in accordance with the Clinical and Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
16
1
3
Order By: Relevance
“…After that, this pathogen has been periodically isolated from clinical samples, including outbreaks, in different states of Brazil [27,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…After that, this pathogen has been periodically isolated from clinical samples, including outbreaks, in different states of Brazil [27,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, enterococcal infections have increased and E. faecalis accounts for the majority of enterococcal infections [19] . Our data suggested that the susceptibility rate to LVFX in E. faecalis in complicated UTI significantly decreased in the most recent 3 years compared to the previous 3 years and the susceptibility rate of catheterized UTI to LVFX in E. faecalis was significantly lower than non-catheterized UTI (p = 0.0153).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus faecalis is one of the most common pathogens in urinary tract infections (UTIs) (7). Recently, enterococcal infections have increased, and E. faecalis accounts for the majority of enterococcal infections (7).…”
mentioning
confidence: 99%
“…Recently, enterococcal infections have increased, and E. faecalis accounts for the majority of enterococcal infections (7). Fluoroquinolones have been frequently used to treat E. faecalis UTIs, and the emergence of fluoroquinolone-resistant E. faecalis (QREF) strains has recently been reported in several countries (12).…”
mentioning
confidence: 99%